1999
DOI: 10.1037/0894-4105.13.3.404
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of attention in dichotic listening: Differential effects on the detection and localization of signals.

Abstract: In 2 dichotic listening experiments, 96 normal right-handed adults attended selectively to the left and right ear and divided their attention equally between both ears. Participants listened for specified targets and reported the ear of entry. The material consisted of pairs of consonant-vowel syllables in Experiment 1 and pairs of rhyming consonant-vowel-consonant words in Experiment 2. Both experiments yielded a right-ear advantage for detection and for localization. Attention instructions had no effect on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 55 publications
2
29
0
Order By: Relevance
“…This might be due to a tendency of the participant to attribute targets to the attended ear irrespective of the actual ear of presentation. Indeed, it has been found that shifting attention to one ear selectively results in a response bias such that stimuli are more often attributed to the attended ear than to the unattended ear (Hiscock, Inch, & Kinsbourne, 1999a, 1999b. In this view, elderly might have an increased response bias to attribute digits to the attended ear that might be due to difficulties in intentionally controlling attention.…”
Section: Increased Localisation Errors In the Elderlymentioning
confidence: 98%
“…This might be due to a tendency of the participant to attribute targets to the attended ear irrespective of the actual ear of presentation. Indeed, it has been found that shifting attention to one ear selectively results in a response bias such that stimuli are more often attributed to the attended ear than to the unattended ear (Hiscock, Inch, & Kinsbourne, 1999a, 1999b. In this view, elderly might have an increased response bias to attribute digits to the attended ear that might be due to difficulties in intentionally controlling attention.…”
Section: Increased Localisation Errors In the Elderlymentioning
confidence: 98%
“…Research going back to the 1960s using dichotic listening tasks has demonstrated a consistent right ear advantage (REA) in reporting words using both auditory-alone (e.g., Broadbent & Gregory, 1965; Hiscock, Inch, & Kinsbourne, 1999), and auditory-visual (Thompson, Garcia, & Malloy, 2007; Thompson & Guzman, 1999) speech stimuli, reflecting left hemisphere specialization for linguistic processing. Grimshaw, Kwasny, Covell, and Johnson (2003) recently reported evidence in a dichotic listening paradigm favoring a direct access interpretation; that is, each hemisphere was found capable of linguistic processing, however, the left hemisphere processed the auditory stimuli faster and more accurately.…”
Section: Lateralization Of Emotion and Language Processing: Behavioramentioning
confidence: 99%
“…This statement is supported by the finding that improvement of performance with session was significant for both visual fields, although this improvement was more pronounced for the right field. However, this interpretation is speculative and work similar to that undertaken by Hiscock et al (1999) in dichotic target localisation would likely provide useful information on the allocation of attention in visual target detection in the divided visual field paradigm. In particular, Hiscock et al (1999) had participants localise a target word or syllable in two separate dichotic listening experiments and manipulated attention allocation by instructing participants to attend to both ears (divided attention), attend to the left ear (focused left), or attend to the right ear (focus right).…”
Section: Voyer and Bolesmentioning
confidence: 89%
“…It is plausible to believe that the presentation of two stimuli simultaneously in dichotic listening forces one to divide attention to some extent between the ears in order to obtain optimal performance. This would presumably provide some control of the aforementioned idiosyncratic attention deployment strategies (but see Bryden, Munhall, & Allard, 1983;Hiscock, Inch, & Kinsbourne, 1999).…”
mentioning
confidence: 99%